Mapping of Nanotechnology Research in Animal Science: Scientometric Analysis - Kutty Kumar (Universitas Pendidikan Indonesia (UPI), 2021)
This paper investigated the development example of nanotechnology from 2005 to May 2019 (15 years). The PubMed database has been utilized to recognize the job of Nanotechnology applications. Absolutely, 502 articles gathered including examination, survey and clinical preliminary were investigated, and the information are introduced in various table headings. Single-wrote papers with 48% of commitments have overwhelmed this field of research. US rules with huge commitments right now followed by England (26%). Dominant part of the productions were in English language (99%) and simply 0.2% distributed in the Chinese. It was intriguing to note 56% research articles were distributed right now. 5% productions were result of clinical preliminaries. The outcomes recommended that creator profitability dissemination anticipated for non-subject in Animal science. From this examination, analysts, researchers, subject masters, understudies, overseers, strategy creators, academicians, Library and Information Science experts and staff partners will be profited attributable to the logical and powerful examination.